TSNAXIP1 is required for sperm head formation and male fertility - Tasrin Sultana; Tokuko Iwamori; Naoki Iwamori (Reproductive Medicine and Biology, 2023)
Abstract Purpose TRANSLIN (TSN) and its binding partner TSNAX have been reported to contribute to a wide spectrum of biological activities including spermatogenesis. TSN accompanies specific mRNA transport in male germ cells through intercellular bridges. A testis‐expressed protein TSNAXIP1 was reported to interact with TSNAX. However the role of TSNAXIP1 in spermatogenesis remained unclear. This study aimed to elucidate the role of TSNAXIP1 in spermatogenesis and male fertility in mice. Methods TSNAXIP1 knockout (KO) mice were generated using the CRISPR‐Cas9 system. The fertility, spermatogenesis, and sperm of TSNAXIP1 KO males were analyzed. Results TSNAXIP1, and especially its domains, are highly conserved between mouse and human. Tsnaxip1 was expressed in testis, but not in ovary. TSNAXIP1 KO mice were generated, and TSNAXIP1 KO males were found to be sub‐fertile with smaller testis and lower sperm count. Although no overt abnormalities were observed during spermatogenesis, lack of TSNAXIP1 induced sperm head malformation, resulting in a unique flower‐shaped sperm head. Moreover, abnormal anchorage of the sperm neck was frequently observed in TSNAXIP1 null sperm. Conclusion A testis‐expressed gene TSNAXIP1 has important roles in sperm head morphogenesis and male fertility. Moreover, TSNAXIP1 could be a causative gene for human infertility.